Royal jelly regulates the caspase, Bax and COX-2, TNF-? protein pathways in the fluoride exposed lung damage in rats - Aslan, Abdullah; Gok, Ozlem; Beyaz, Seda; Can, Muhammed Ismail; Parlak, Gozde; Gundogdu, Ramazan; Baspinar, Serpil (Churchill Livingstone, 2022)
The study was carried out on 42 male rats divided into six groups with 7 rats in each group: two control groups, two injury groups and two treatment groups. One of the control groups received a basal diet while the other one was fed a basal diet supplemented with royal jelly (RJ) (100 mg/kg). The two injury groups were given 50 mg/kg and 100 mg/kg fluoride, respectively. The two treatment groups exposed to 50 mg/kg and 100 mg/kg fluoride were both fed basal diets with RJ (100 mg/kg). Lungs were taken for histopathological examination. Spectrophotometric analysis was utilized to determine Malondialdehyde (MDA), catalase (CAT) and glutathione (GSH) activities, and Western blotting technique was used to evaluate the levels of specific proteins. On one hand, our experiments revealed that RJ caused decreased MDA levels, and downregulation of COX-2, Bcl-2, GSK3 and TNF?? protein expressions. On the other hand, rolay jelly caused augmented GSH and CAT activities, as well as upregulated Bax, BDNF, caspase-3, caspase-6, caspase-9 protein expressions in rats injuried by the fluoride exposure. The results suggest that the application of RJ was very likely to have a healing effect on the degenerative changes seen in the examined tissue.
Keywords: Apoptosis; Lung; NaF; ROS; Royal jelly